Penerapan aplikasi digital dalam penyusunan laporan keuangan pada usaha mikro: Studi kasus pada 7W Coffee - Pontoh, Natasha Maria Angela; Gamaliel, Hendrik; Kapojos, Peter M. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Information technology has a significant impact on Accounting Information Systems (AIS) in Micro, Small and Medium Enterprises (MSMEs). One application that has been developed is "AkuntansiKu" which can assist in presenting financial reports programmed into the application system, such as the Income Statement, Statement of Changes in Capital, and Cash Flow Statement. This study aims to investigate whether the application of digital applications can facilitate the presentation of financial statements in accordance with standards. The analysis method used is descriptive qualitative analysis by collecting data through interviews. The results showed that the application of digital applications such a s "AkuntansiKu" can help MSMEs in presenting complete financial reports and in accordance with standards. This provides great benefits for companies in producing an easier recording process and accountable reporting.